(untitled) (The Pakistan Development Review, 1982)
This should be counted among the better books published on Pakistan’s economy in that it is analytical and not merely descriptive. That the book’s contents may not match the expectations created by its title reflects not the author’s failing alone, but also the fragmented state of information about the economy itself. I think Professor Naseem has made good use of the available data, although in places his argument is tedious and merely rhetorica1. The book covers a large number of issues, and brings together the author’s published and unpublished research in these areas. While it does not have a definite focus, it articulates a point of view, which is critical of the dominant ideology of growthmanship through private enterprise and the consequent foreign-sector orientation of the economy, neglecting the real issues of structural change and equity. He even castigates the short-lived experiment of "socialism" in the early Seventies as whimsical and ad hoc.